Letter from Percy L. Julian to Bernhard Witkop - Julian, Percy Lavon (1949)
Concerns Robert B. Woodward's synthesis of methochloride of sempervirine. Also discusses an error made by Julian in the lab and communicated to Witkop in an earlier letter.
Keywords: Prelog, V. (Vladimir), 1906-1998; Glidden Company; Woodward, R. B. (Robert Burns), 1917-1979; Julian, Percy Lavon, 1899-1975; Chemistry, Organic; Organic compounds--Synthesis; Witkop, Bernhard, 1917-